A framework of flexible locally resonant metamaterials for attachment to curved structures. (15th August 2021) - Yu, Junmin; Nerse, Can; Chang, Kyoung-jin; Wang, Semyung
Highlights: We propose a flexible locally resonant metamaterial design that can be applied to curved surfaces. Owing to modular and flexible design, the proposed structure is independent of the host curvature. Numerically and experimentally band gap is identified. Compared to a traditional damping treatment our flexible metamaterial design is shown to be superior. Flexible design is expected to be broadly applicable as an NVH solution. Abstract: Locally resonant metamaterials (LRMs) have been extensively investigated for their superior attenuation performance in the band gap frequencies despite not resulting in a large mass increase, comparatively. However, for their application on actual industrial structures, there exist limitations, the most important of which is the flexibility of the LRM structure. Several studies have succeeded in attaching LRMs to curved surfaces, but if the curvature changes, the unit structure must be redesigned. In this paper, a flexible LRM design independent of curvature is proposed, and numerical simulations illustrate the implementation of the band gap in a beam. Proof of concept of the flexible LRM has been shown through modal experiments on various curved surfaces. Excellent attenuation characteristics of the flexible LRM are demonstrated via a comparison with a constrained layer damping treatment, which are typically considered in noise, vibration and harshness (NVH) area. As the proposed flexible LRM can be attached to various curvatures without restriction or redesign, it differentiates itself as a practical alternative to other LRM designs and expected to be explored in diverse applications. Graphical abstract: Image, graphical abstract